The Success Rate of Cryopreservation and Thawing of Embryos at Day 3 and Day 5 Following Intracytoplasmic Sperm Injection (ICSI) - Ria Margiana; Maitra Djiang Wen (Jurnal Penelitian Pendidikan IPA, 2024)
Cryopreservation, the technique of freezing and thawing embryos, is essential in in vitro fertilization (IVF) treatments to ensure the long-term preservation of embryos for future use. This innovative study evaluates the effectiveness of these procedures conducted at a private hospital in Tangerang, Indonesia, over a period of seven years (2016-2023), involving 18,000 couples. The design research was conducted retrospectively. The study examined embryos that underwent cryopreservation and subsequent thawing, with data collected on the rates of cell division observed on Day 3 and the rates of blastocyst formation on Day 5 after thawing. The study investigated the rates of cellular division on Day 3 and the development of blastocysts on Day 5 following the thawing process. The findings demonstrated a remarkable cleavage rate of 95.24% and a blastocyst rate of 97.22%. The remarkable results underscore the efficacy of the advanced freezing and thawing techniques employed. This discovery is highly significant since there is an urgent requirement to improve the success rates of in vitro fertilization (IVF) for couples facing infertility. It offers a fresh sense of hope and increased opportunities for establishing successful pregnancies with the improvement of cryopreservation techniques.